2009
DOI: 10.1182/blood-2008-10-184234
|View full text |Cite
|
Sign up to set email alerts
|

A novel variant on chromosome 7q22.3 associated with mean platelet volume, counts, and function

Abstract: Mean platelet volume (MPV) and platelet count (PLT) are highly heritable and tightly regulated traits. We performed a genomewide association study for MPV and identified one SNP, rs342293, as having highly significant and reproducible association with MPV (per-G allele effect 0.016 ؎ 0.001 log fL; P < 1.08 ؋ 10 ؊24 ) and PLT (per-G effect ؊4.55 ؎ 0.80 10 9 /L; P < 7.19 ؋ 10 ؊8 ) in 8586 healthy subjects. Whole-genome expression analysis in the 1-MB region showed a significant association with platelet transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 49 publications
(63 reference statements)
10
108
0
1
Order By: Relevance
“…However, MPV displayed an inverse correlation with platelet count, showing an increase with age that was most pronounced in early childhood, consistent with previous studies (1,24 ). Moreover, genomewide association studies have found that regulation of platelet count and volume in healthy individuals may occur as a result of highly heritable traits between individuals due to single nucleotide polymorphisms (28 ) in several genes that regulate megakaryopoiesis and proplatelet formation (29 ). Indeed, this genetic variability could explain the dynamic fluctuations in platelets across age groups in Canada, which is a diverse multiethnic population.…”
Section: Discussionsupporting
confidence: 77%
“…However, MPV displayed an inverse correlation with platelet count, showing an increase with age that was most pronounced in early childhood, consistent with previous studies (1,24 ). Moreover, genomewide association studies have found that regulation of platelet count and volume in healthy individuals may occur as a result of highly heritable traits between individuals due to single nucleotide polymorphisms (28 ) in several genes that regulate megakaryopoiesis and proplatelet formation (29 ). Indeed, this genetic variability could explain the dynamic fluctuations in platelets across age groups in Canada, which is a diverse multiethnic population.…”
Section: Discussionsupporting
confidence: 77%
“…34 Associations at the WDR66 locus As with other hematological traits, GWAS have successfully identified the genetic loci associated with PLT-related traits. 24,27,28,32,34,38,43 The initial GWAS for MPV was conducted in European populations and identified WDR66, ARHGEF3 and TAOK1 as candidate genes responsible for the regulation of PLT. 24 Of these, a variant located in the genetic region of WDR66 showed the most significant association, explaining approximately 2.0% of the inter-individual variance in MPV.…”
Section: Genetic Factors For Pltmentioning
confidence: 99%
“…[1][2][3][4][5] As part of this effort, we previously identified a panel of platelet membrane proteins that were expressed more highly in MKs and resting endothelial cells (ECs) than in other blood cell lineages, but with hitherto unknown roles in platelet function or thrombus formation. 6 Of the 279 genes identified, 4 (including bone morphogenetic protein and activin membrane-bound inhibitor [BAMBI]) were selected for functional analysis in zebrafish.…”
Section: Introductionmentioning
confidence: 99%